Molecular cloning and extracellular expression of cyclodextrin glycosyltransferase gene from Bacillus sp. NR5 UPM - Ramli, Norhayati; Abd. Aziz, Suraini; Hassan, Mohd Ali; Mohammed Alitheen, Noorjahan Banu; Kamaruddin, Kamarulzaman; Ibrahim, Zoolhilmi (Academic Journals, 2011)
The cloning of a polymerase chain reaction (PCR) gene fragment from Bacillus sp. NR5 UPM isolated from the soil in Malaysia into an Escherichia coli expression vector was successfully carried out. Analysis of the nucleotide sequences revealed the presence of an open reading frame of 2112 bp which encoded a protein containing 704 amino acids with a putative molecular weight of 78.6 kDa. The deduced amino acids sequence showed about 98% homology with the CGTase from Bacillus sp. KC201. Compared to the wild type, the CGTase that was produced in E. coli cells only required one-fourth of culture time and neutral pH to produce CGTase. After 12 h of cultivation, the CGTase activity in the culture medium reached 29.6 U/ml, which was approximately 2.5-fold higher than the CGTase from the parental strain. The CGTase was produced extracellularly by E. coli (94%) indicating the signal peptide was functional in E. coli.